POTENSI SUMBER PANGAN LOKAL DI KAWASAN KHDTK MUNGKU BARU - Pienyani Rosawanti; Nurul Hidayati; Nanang Hanafi (Lambung Mangkurat University-Indonesia, 2021)
The current pandemic of the Corona-19 virus not only affects social activities but also affects the food sector. Strong food security in the long term can be realized through a diversification program based on local wisdom by utilizing local plants. This study aims to determine the potential of local food sources that can be used as an alternative to food consumption in the regions and reduce dependence on food sources from outside the region in realizing food security during and after the Covid-19 pandemic (study on communities in the Mungku Baru Educational Forest area, Muhammadiyah University. Palangkaraya). The research was conducted in the educational forest area or Forest Area with Special Purpose (KHDTK), Mungku Baru Village, Rakumpit District, Palangka Raya City, Central Kalimantan Province. The research method is descriptive qualitative from the results of interviews. Data analysis using tabulation matrix. There are 33species of local plants used by the community. Utilization of these plants in the form of fruit, seed, peel of fruit, leaves, rubers, and young shoots by eating or cooking them. Cultivation has not been carried out, the community takes directly part of the plant to be consumed. Habitus of these plants in the form of trees, shrubs, lianas, grasses, shrubs and herbs. Existing local food sources can be used as an alternative for food consumption in the regions and reduce dependence on food sources from outside the region and can realize food security during and after the Covid-19 pandemic